A Systematic Review Examining the Relationship Between Habit and Physical Activity Behavior in Longitudinal Studies - Feil, Katharina; Allion, Sarah; Weyland, Susanne; Jekauc, Darko (Frontiers in Psychology, 2021)
Purpose: To explain physical activity behavior, social-cognitive theories were most commonly used in the past. Besides conscious processes, the approach of dual processes additionally incorporates non-conscious regulatory processes into physical activity behavior theories. Habits are one of various non-conscious variables that can influence behavior and thus play an important role in terms of behavior change. The aim of this review was to examine the relationship between habit strength and physical activity behavior in longitudinal studies. Methods: According to the PRISMA guidelines, a systematic search was conducted in three databases. Only peer-reviewed articles using a longitudinal study design were included. Both, habit and physical activity were measured at least once, and habit was related to physical activity behavior. Study quality was evaluated by assessment tools of the NHLBI. Results: Of 3.382 identified publications between 2016 and 2019, fifteen studies with different study designs were included. Most studies supported that positive correlations between habit and physical activity exist. Some positive direct and indirect effects of habit on physical activity were detected and only a minority of studies showed the influence of physical activity on habit strength. Studies differentiating between instigation and execution habit found positive correlations and revealed instigation habit as a stronger predictor of physical activity. The quality of studies was rated as reasonable using assessment tools of the NHLBI. Conclusion: This review revealed a bidirectional relationship between habit and physical activity. Whether habit predicts physical activity or vice versa is still unclear. The observation of habit influencing physical activity may be most appropriate in studies fostering physical activity maintenance while the influence of physical activity on habit may be reasonable in experimental studies with physical activity as intervention content to form a habit. Future investigations should differentiate between habit formation and physical activity maintenance studies depending on the research objective. Long-term study designs addressing the complexity of habitual behavior would be beneficial for establishing cue-behavior associations for the formation of habits. Furthermore, studies should differentiate between instigation and execution habit in order to investigate the influence of both variables on physical activity behavior independently.